Exploring the Implementation and Outcomes of a Digital Storytelling Project in an EFL Secondary School Speaking Class - Imama, Puja; Pusparini, Ririn (English Education:Journal of English Teaching and Research, 2025)
This study addresses the limited understanding of how digital storytelling projects are implemented in secondary EFL speaking classes, despite their recognized potential for fostering communicative and creative learning. It explores the implementation process and outcomes of a Digital Storytelling Project (DSTP) conducted in an Indonesian EFL secondary school. Using a qualitative interpretive case study design, data were gathered through classroom observations and rubric-based assessments involving one English teacher and twenty-one eighth-grade students divided into four groups. The analysis revealed that DSTP was carried out through three main stages, including planning, implementing, and reporting, with varying degrees of teacher facilitation. The project stimulated students’ engagement, collaboration, and creativity. However, insufficient scaffolding and unclear guiding questions during the planning phase affected project coherence and duration. Students’ speaking performance improved particularly in fluency and pronunciation, while issues remained in content clarity and narrative structure. Overall, DSTP provided meaningful opportunities for authentic language use and collaborative learning. The study concludes that digital storytelling, when implemented with adequate instructional scaffolding, can serve as a pedagogically rich medium for teaching speaking and aligns with the principles of Indonesia’s Independent Curriculum emphasizing creativity, collaboration, and student agency.